Increased Expression of Interleukin (IL)‐35 and IL‐17, But Not IL‐27, in Gingival Tissues With Chronic Periodontitis. Issue 2 (1st February 2015) - Mitani, Akio; Niedbala, Wanda; Fujimura, Takeki; Mogi, Makio; Miyamae, Shin; Higuchi, Naoya; Abe, Atsushi; Hishikawa, Toshimitsu; Mizutani, Makoto; Ishihara, Yuichi; Nakamura, Hiroshi; Kurita, Kenichi; et al.
Abstract : Background: Interleukin (IL)‐35 plays an important role in immune regulation through the suppression of effector T‐cell populations, including T‐helper 17 (Th17) cells. Although Th17 cells and IL‐17 are involved in the pathogenesis of periodontitis, the level of IL‐35 in inflamed periodontal tissues is unclear. Here, IL‐35, IL‐17, and IL‐27 production/expression in gingival crevicular fluid (GCF) and human gingival tissue were investigated. Methods: GCF samples were collected from buccal (mesial, center, and distal) sites of teeth from patients with chronic periodontitis (CP) and healthy controls and were analyzed by enzyme‐linked immunosorbent assay for IL‐35 (periodontitis, n = 36; healthy, n = 30) and IL‐17 (periodontitis, n = 16; healthy, n = 13). Gingival tissue, including sulcus/pocket epithelium and underlying connective tissue, was collected from an additional 10 healthy participants and 10 patients with CP and were analyzed by quantitative polymerase chain reaction (qPCR) for Epstein Barr virus‐induced gene 3 ( EBI3 ), IL12A, and IL17A. IL27p28 was also tested by qPCR. Results: IL‐35 and IL‐17 were significantly higher in GCF from patients with periodontitis than healthy participants ( P <0.01, P <0.05, respectively). In both healthy participants and those with periodontitis, positive correlations were found among IL‐35 and probing depth and clinical attachment level (CAL) as well as between IL‐17 and CAL. EBI3, IL12A (components of IL‐35), and IL17A messenger RNA expression levels were significantly higher in inflamed gingival tissue than in healthy control tissues ( P <0.05). IL27p28 was not detected in any sample, suggesting that IL‐27 is not produced in large quantities in periodontal tissue. Conclusion: IL‐35 and IL‐17, but not IL‐27, may play important roles in the pathogenesis of periodontitis.